Nocturnal camouflage through background matching against moonlight - Juan J. Negro; Salvador Bará; David Galadí-Enríquez; Juan Luis Nieves; Miguel A. Martínez-Domingo; Alejandro Ferrero; Joaquín Campos; Carmen Bao-Varela; Eduard Masana; Carlos Camacho (Proceedings of the National Academy of Sciences, 2025)
Camouflage is often considered a daytime phenomenon based on light and shade. Nocturnal camouflage can also occur, but its mechanistic basis remains unclear. Here, we analyze the conditions for background matching (BM) of avian predators against the night sky. Such concealment is achieved when the contrast between the predator and the sky is smaller than the contrast detection threshold of prey. This condition cannot be fulfilled under isotropic skies, as in fully overcast or moonless nights. However, on clear moonlit nights, the isotropy of the sky radiance is broken due to the presence of the Moon, and the conditions for BM can be met for a wide range of sky directions. This effect is mainly dependent on the altitude of the Moon above the horizon, rather than on Moon phase. We have modeled the feasibility of concealment through BM of a typically white barn owl ( Tyto alba ) when hunting rodents, based on its contrast against the moonlit sky. We considered the radiometric quantities of the sky, the ground, and the bird’s undersides. Our results show that a barn owl with highly reflecting underparts may approach a rodent from broad regions of the moonlit sky while keeping itself below the contrast detection threshold of the mouse M-cones and rods. S-cones, in turn, remain below their excitation threshold for most of the lunar cycle. Our results demonstrate that the white color of barn owls serves as camouflage tailored to the moonlit sky background, providing a mechanistic basis for understanding nocturnal camouflage.